Growth and yield performance of garlic varieties under zero-tillage and tillage system - Rahman, M. M.; Hossain, M.; Rahman, M. H.; Rahim, M. A.; Islam, M. T. (International Journal of Horticultural Science, 2020)
Bangladesh Agricultural University (BAU) developed four garlic variety viz., BAU Garlic-1; BAU Garlic-2; BAU Garlic-3; and BAU Garlic-4 were tested under two cultivation systems viz., zero-tillage and tillage to find out a suitable variety for zero-tillage system. This study was conducted following randomized complete block design with three replicates. Results showed that planting system had significant influenced on growth, yield contributing traits and bulb yield of garlic. It was also observed that all the studied traits were higher in zero-tillage condition as compared to tillage system. There were significant variations noticed among the garlic varieties on plant growth and yield traits. However, in combination of planting system and variety, it was found that BAU Garlic-3 performed superior on plant growth and bulb yield of garlic under zero-tillage system. From the findings of this study, it can be concluded that BAU Garlic-3 could be useful technology for cultivation of garlic in zero-tillage system.